2020
DOI: 10.3389/fcvm.2020.594788
|View full text |Cite
|
Sign up to set email alerts
|

Does Serum Uric Acid Status Influence the Association Between Left Atrium Diameter and Atrial Fibrillation in Hypertension Patients?

Abstract: Objective: Both serum uric acid (SUA) levels and left atrium diameter (LAD) associate with AF. However, the influence of SUA status for the associated risk of AF related to LAD in hypertension patients is currently unknown.Methods: We retrospectively analyzed a hospital-based sample of 9,618 hypertension patients. Standard electrocardiograms were performed on all patients and were interpreted by expert electro-physiologists.Results: Overall 1,028 (10.69%) patients had AF out of 9,618 patients. In men >6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…HF was defined based on the presence of symptoms of HF and evidence of at least one echocardiographic abnormality (17). Patients were diagnosed with atrial fibrillation (AF) if they met any of the following criteria: (1) AF pattern in baseline 12lead electrocardiogram (ECG) screening or (2) AF episodes in 24-hour single-lead ECG recording or Holter (18). We defined the first signs of AF during hospitalization as the incident AF cases.…”
Section: Definition Of Cardiovascular Comorbiditymentioning
confidence: 99%
“…HF was defined based on the presence of symptoms of HF and evidence of at least one echocardiographic abnormality (17). Patients were diagnosed with atrial fibrillation (AF) if they met any of the following criteria: (1) AF pattern in baseline 12lead electrocardiogram (ECG) screening or (2) AF episodes in 24-hour single-lead ECG recording or Holter (18). We defined the first signs of AF during hospitalization as the incident AF cases.…”
Section: Definition Of Cardiovascular Comorbiditymentioning
confidence: 99%
“…Standard two-dimensional echocardiography with Doppler examination was performed, and measurements were obtained according to the guidelines of the American Society of Echocardiography ( 20 ). The left atrium diameter was obtained as previously reported ( 21 ), and LAE was defined on the basis of a posteroanterior dimension >35 mm. The left ventricular mass was measured by echocardiography, and the left ventricular mass index was calculated ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, considerable attention has been obtained to the possible mechanism by which hyperuricemia contributes to AF 14 , 15 . Several studies reported that there was an association between elevated SUA and the risk of AF 16 18 , while results remained an inconclusive measurement, possibly due to differences in the study population, confounding factors, or gender. To our knowledge, studies on different subtypes of relationships between SUA levels and AF are limited, and the potential relationship between paroxysmal AF and SUA levels has not been fully elucidated, especially in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%